Study of prescription pattern in a tertiary care hospital in Chhattisgarh, India: an observational study - Raj, Purnima; Choudhury, Subhankar; Kundu, Sumati; Patel, Satyam; Sidar, Bhagwati (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Prescription audit is one of the methods to assess the drug utilization pattern and rational use of drugs. In our country the value of drugs prescribed is in crores but a significant proportion of drugs is prescribed irrationally. This is probably due to defect in prescription pattern, lack of knowledge in health care personnel, pressure from drug manufacturing companies and many more. To promote rational use of drugs, standard policies must be set and this can be achieved only after auditing current prescription practices. Methods: A prospective study was carried out in Medical college hospital, Raigarh in the month of January 2018. Around 1000 prescriptions were collected randomly from pharmacy and the prescriptions were analysed on various parameters like patient’s demography, parts of a prescription, information related to doctor and drugs. Results: In this study, we found that percentage of generic drugs were 58.02% and 70.43% drugs were from essential drug list. Only 13.19% FDCs were used. 34 prescriptions were illegible and capital letters were used only in 26 prescriptions. We also found deficiency in parts of a prescription like inscription part (13.3%), subscription part (26.9%) and in doctor’s identity (33.2%). The majority of drugs were antimicrobials (23.81%) followed by anti-inflammatory and analgesics (21.1%). Conclusions: This study shows that the use of generic drugs and essential drugs is on the lower side as compared to standard guidelines. The prescription pattern was defective in many prescriptions. This study shows incompleteness of prescriptions and proper steps are needed to guide the physicians to promote rational use of drugs.